Self-assembly of HPW on Pt/C nanoparticles with enhanced electrocatalysis activity for fuel cell applications - Wang, D.; Lu, S.; Xiang, Y.; Jiang, San Ping (elsevier, 2011)
We report here a novel method to immobilize water soluble tungstophosphoric acid (H3PW12O40, HPW) on Pt/C nanoparticles via the electrostatic interaction between the negatively charged HPW and the positively charged functional groups of chitosan which has been attached to Pt/C nanoparticles to provide positively charged sites for the self-assembly of HPW. The HPW assembled Pt/C catalysts (donated as Pt/C-chitosan-HPW) were characterized by XRD, FTIR, TGA, zeta potential, and X-ray photoelectron spectroscopy (XPS). The results indicate that HPW assembled on chitosan-functionalized Pt/C is very stable and Pt/C-chitosan-HPW catalyst has a higher utilization efficiency as compared to that of pristine Pt/C catalyst. Electrochemical activity of Pt/C-chitosan-HPW catalysts for methanol oxidation and oxygen reduction reaction (ORR) is significantly higher than that of Pt/C catalysts without assembled HPW. The enhanced electrocatalytic activities of HPW assembled Pt/C catalysts are most likely due to the synergistic effect between assembled HPW and Pt/C nanoparticles and the presence of HPW leads to a downward shift in the d-band center of Pt catalyst and facilitates the oxidative removal of COads poisoning species for methanol oxidation and desorption of Oads species for ORR on Pt catalysts.